High-mobility group box 1 is associated with neurological outcome in patients with post-cardiac arrest syndrome after out-of-hospital cardiac arrest. Issue 1 (December 2016) - Omura, Taku; Kushimoto, Shigeki; Yamanouchi, Satoshi; Kudo, Daisuke; Miyagawa, Noriko
Abstract Background Alarmins, including high-mobility group box 1 (HMGB-1), can be released from damaged tissues and activated cells as inflammatory mediators. We aimed to evaluate HMGB-1 and mitochondrial DNA dynamics and estimate the prognostic value for neurological outcome in patients with post-cardiac arrest syndrome after out-of-hospital cardiac arrest. Methods We evaluated the dynamics of HMGB-1, mitochondrial DNA, and other variables in patients with return of spontaneous circulation after out-of-hospital cardiac arrest. Patients were divided into two groups according to the cerebral performance category at 30 days: the favourable outcome group (cerebral performance categories 1 and 2) and unfavourable group (≥3). Results Twenty-one patients were included, and 11 demonstrated favourable outcomes. HMGB-1 levels and mitochondrial DNA on day 1 were significantly higher than on days 2, 3, 5, and 7. Plasma levels of HMGB-1 on day 1 correlated with prognostic parameters (estimated interval to return of spontaneous circulation, lactate, and NH3), tissue damage, systemic inflammation, and disease severity. HMGB-1 on day 1 in the unfavourable group was significantly higher than in the favourable group (median [interquartile range] 15.5 [6.65–18.7], 39.4 [17–69.5], P  = 0.009). These findings were not observed regarding mitochondrial DNA. Regarding HMGB-1 prediction accuracy for a good neurological outcome, the area under the receiver operating characteristic curve was 0.864 (95 % confidence interval 0.702, 1.000). Conclusions HMGB-1 may be involved in acute-phase post-cardiac arrest syndrome pathophysiology, and an increase in plasma levels may be associated with a poor neurological outcome. The study was registered with the University Hospital Medical Information Network Clinical Trials Registry ID: UMIN000006714.